Aplikasi Teknologi Satelit dalam Penanggulangan Bencana: Perspektif Sains Geospasial dan Resiliensi Nasional - Pratiwi, Ire; Supriyadi, Asep Adang; Prihanto, Yosef (UNIB Press, 2026)
Climate change, geological activity, and environmental degradation have increased the number of natural disasters in recent years. To mitigate the social, economic, and infrastructure impacts, early disaster detection and mitigation are crucial. Real-time monitoring of geospatial phenomena such as forest fires, floods, and landslides is aided by satellite technology. Combining remote sensing technology with big data and artificial intelligence improves prediction accuracy and enhances rapid disaster response. In addition to disaster mitigation, satellite technology contributes to national resilience by monitoring geospatial threats and regional security, including border surveillance and cyber threat detection. The development of satellite technology in Indonesia faces constraints such as limited budget and human resources, but through strategic investment and collaboration, there is significant potential to increase its independence and resilience. Satellite technology is expected to strengthen national resilience and support sustainable development and public welfare in the face of global threats.